Akulturasi Budaya Arab dan Lokal dalam Membangun Harmoni Sosial Pada Masyarakat Demangan Bondowoso - Asfiyah, Wardatul (Mozaic: Islamic Studies Journal, 2022)
There are two ethnic groups living in Kademangan, namely Arabs and local residents. Arab groups and local communities have different cultures that interact continuously so that cultural acculturation occurs. With the adjustment, it will create a good relationship between the Arab community and the local population. This acculturation then created a harmonious relationship between the local population and the Arab community in Kademangan Bondowoso Village. Social harmony exists in various aspects, both in terms of religion and social relations between the Arab Community and the local population. This research tries to answer the acculturation of Arabic and local languages ​​as a form of social harmonization in the people of Kademangan Bondowoso. This study results that the Kademangan community consists of Arab ethnicity and local residents, causing friction between two different cultures. Cultural contacts that occur continuously, make one of them have to adapt. Arab groups as immigrants must of course adapt to the habits of the local community, one of which is language. The local language is Madurese. Meanwhile, the Arab community's native language is Arabic. As a form of acculturation with the local community, ethnic Arabs made language adjustments so that a mixture of Arabic and Madurese was created.